IMPLEMENTASI ASSESMEN NASIONAL BERBASIS KOMPUTER (ANBK) TERHADAP MUTU SEKOLAH SDN CAKUNG BARAT 03 JAKARTA TIMUR - Ani Nuraini; Nurrohmatul Amaliyah; Abd.Rahman A.Ghani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study is motivated by the importance of implementing the Computer-Based National Assessment (ANBK) as an effort to improve the quality of education, although its implementation at the elementary school level still faces several challenges. The purpose of this study is to describe the implementation of ANBK in improving educational quality at SDN Cakung Barat 03, as well as to identify the obstacles, stakeholder motivation, and its impact on school quality. This study employed a qualitative descriptive approach, with data collected through observation, interviews, and documentation. Data analysis was conducted using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The results indicate that the implementation of ANBK at SDN Cakung Barat 03 has been carried out fairly well and has had a positive impact on improving the quality of education, particularly in literacy, numeracy, and strengthening a data-driven evaluation culture. However, several challenges remain, such as limited infrastructure, technological readiness, and human resource competence. In addition, the motivation of the principal and teachers plays a significant role in supporting the success of ANBK implementation. Efforts to improve quality are carried out through enhancing teachers’ competencies in developing literacy- and numeracy-based assessment items, strengthening school digitalization through training programs, and optimizing infrastructure and school management. Therefore, the implementation of ANBK contributes to the continuous improvement of educational quality.